Racial Bias in Academia: An Audit Experiment Revealing Disparities in Faculty Responses to Prospective Students - Goldsmith, Benjamin E.; MacKenzie, Megan; Wynter, Thomas (International Journal of Education Policy and Leadership, 2024)
Building on Milkman, Akinola, and Chugh (2015), this article presents data from an experiment conducted in Australia that included fictional emails from prospective students seeking a meeting with faculty members. The results show significantly different responses from faculty depending on the student’s name and association with a racialized group. While the study reveals evidence of racial bias, there is, contrary to previous studies, little evidence of gender bias. Additionally, the study concludes that gender or racial diversity at the university or discipline level is not associated with lower rates of bias. Additional exploratory analysis further examines the data for evidence of change processes, including the interaction of gender and racial diversity, and lower rates of bias among more junior academics.